Banished to the Great Northern Wilderness : Political Exile and Re-education in Mao's China - Wang, Ning, 1964- (Book collections on Project MUSE., 2017)
"Wang examines the ways in which the state sought to re-educate the intellectuals at army farms and labour camps, and the strategies the exiles used to deal with camp officials and improve their chances of survival. While banished intellectuals were victims of the campaign, some also became perpetrators of injustice themselves who betrayed their friends and comrades. Isolated in a desolate northern borderland and subject to physical and psychological abuse, the exiles often denounced each other and, for self-preservation, declared allegiance to the state. Including interviews with former "rightists" and even a camp guard, Banished to the Great Northern Wilderness shines a bright light on the exile communities, social conflicts, and history of the early PRC."--